PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN BARRU KABUPATEN BARRU - Hafsah Hafsah; Harlindah Harniati Arfan; Muhammad Idris (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2022)
This study aims to analyze the effect of 1) transformational leadership, competence and work motivation partially on employee performance 2) transformational leadership, competence and work motivation simultaneously on employee performance 3) which variables among transformational leadership, competence and work motivation have the most influence dominant on employee performance at the Barru District Office, Barru Regency. The research approach used in this study is a quantitative method with a survey approach conducted at the Barru District Office, Barru Regency. The time of the study was carried out from March to April 2022. The research population was all employees at the Barru District Office, Barru Regency, amounting to 54 people. In this study, the sampling technique used was a saturated sample where all members of the population were used as a sample of 54 people. The analysis technique used in this research is instrument test, classical assumption test, multiple regression test, hypothesis test and coefficient of determination test. The results showed that 1) transformational leadership had no significant effect on employee performance, 2) competence had no significant effect on employee performance 3) work motivation had a significant effect on employee performance 4) transformational leadership, competence and work motivation had a significant effect on employee performance. 5) work motivation which has the most dominant influence on employee performance at the Barru District Office, Barru Regency.